A Study on Performance Analysis of Web Services Using Various Tools - Goyal, Shaily; Kaushik, Manju (International Journal of Computer Sciences and Engineering, 2025)
Testing is an important stage of SDLC that determines the performance and accuracy of the software. Performance testing helps to understand the reliability, scalability, responsiveness, and throughput of software under a given workload owing to its popularity. Web services are increasingly used in web applications and testing them is comparatively difficult with regards to traditional applications in terms of unpredictable load, response time etc. This review paper presents a comparative study of web service testing tools by measuring response time and throughput. Moreover, after thorough examination changes are recommended for web services and testing tools.